Investigating difficulties and challenges of university administrators in developing academic branches and increasing research quality and productivity at industrial and non industrial universities(a qualitative study) - Mohammad hassan Pardakhtchi; Akbar Faraji armaki; Saeed Hasanzadeh (آموزش مهندسی ایران, 2011)
Globalization and knowledge-oriented economic development have brought about basic changes in the structure and responsibilities of higher education all over the world. The value of nations mostly depends on their easily accessibility to the management and government rather than material resources. Effective education causes the improvement of scientific foundation; therefore, it plays a significant role in the future development. The strategic thought makes the organizations ready to confront and conform to future conditions successfully. The strategic programs would give a clear picture of moving from the status quo to more favorable situation and provide a better understanding of the environment. So it helps the organization perform more effectively. Thus, it is important to evaluate the organization competitive environment and its strategic position in the strategic planning. The university inputs are finance, building, equipment, program, facilities and human resources and its process includes education, research and providing services, keeping and transferring cultural heritage and technology; its outputs are experts and specialists in innovation, invention, scientific discoveries, production and expansion of knowledge boundaries. However, it does not prepare the effective research conditions because of the inefficiency of academic systems for better output. The old tradition of writing pamphlets is governing the educational system and because of the lack of a well-organized system and wrong policies, university environment is changing into a traditional educational one without productivity. This qualitative research was conducted through structured interviews with experts. Its aim was to identify barriers of effective academic planning and quality and productivity.